Al-Sulṭah al-Ramziyyah li “Rajah” al-Ṣalawāt ‘alā al-Nabī ka-Tamīmah li al-Rawāj ladā al-Bā’i‘īn al-Mutajawwilīn fī Madīnah Pekalongan - Muhandis Azzuhri; Faliqul Isbah; Muhammad Zayinil Akhas; Fina Naila Sakinah (ALSINATUNA, 2026)
There is a shift in values and culture in the phenomenon of 'pesugihan' among traders in Pekalongan City who previously carried out rituals by drawing closer to God through the medium of Mrs. Kaji Dewi Lanjar now shifting into pesugihan rituals by using a tattoo that reads the Prophet's shalawat, symbolic numbers, and symbols. hijaiyah letters with angelic khadam as trading sellers by asking the Ustad/Kyai who is considered to be able to provide a recommendation for the awarding of the penglaris tattoo. The theory used is Peirce 's Semiotics and Bourdieu's symbolic power by revealing the meaning of codes, icons, indexes and symbols in the diagram so that their meanings can be read and Bourde's symbolic power theory where something symbolic can be known through a certain relationship between those who use it. that power. The type of research is field research with data collection through in-depth interviews, participatory observation and documentation with qualitative descriptive analysis techniques. This research aims to uncover the symbolic meanings of certain hijaiyah letters and images in talismanic inscriptions (rajah) among street vendors in Pekalongan. The findings reveal that the text of hijaiyah letters and numbers from Quranic verses, the Prophet’s prayer (Shalawat), and talismanic images are believed to carry business identity, bring good luck, and possess spiritual appeal that directly contributes to business success by being regarded as amulets for attracting customers. The significance of these findings lies in their contribution to expanding Arabic linguistic studies and opening space for critical reflection on the dynamics of meaning of symbolic hijaiyah letter texts in talismanic inscriptions within the economic context of the grassroots community of street vendors.